The Assembly History of Disk Galaxies: II. Probing the Emerging Tully-Fisher Relation During 1 - Miller, S; Ellis, R; Sullivan, M; Bundy, K; Newman, AB; Treu, T (Institute of Physics Publishing, 2012)
Through extended integrations using the recently-installed deep depletion CCD on the red arm of the Keck I Low Resolution Imaging Spectrograph, we present new measurements of the resolved spectra of 70 morphologically-selected star-forming galaxies with i_AB<24.1 in the redshift range 1<z<1.7. 2.2="" 3727="" 42="" [o="" a="" acs="" and="" at="" available="" between="" body="" combining="" construct="" curves="" defined="" derived="" disk="" distribution="" dynamics="" emission="" enables="" extended="" field="" for="" formalism="" from="" galaxies.="" ground-based="" growing="" hst="" i="" ii]="" images,="" in="" integral="" interval="" introduced="" line="" mass="" masses="" measures="" near-infrared="" of="" paper="" photometry="" probed="" radius="" recover="" relation="" resolved="" rotation="" sample="" scale="" series="" spectrographs="" stellar="" successfully="" the="" these="" this="" time="" times="" to="" tully-fisher="" unit="" us="" using="" we="" well-constructed="" with="" z="" z~1="">2. Remarkably, we find a well-defined Tully-Fisher relation with up to 60% increase in scatter and stellar mass zero-point shift constraint of 0.02+/-0.02 dex since z~1.7, compared to the local relation. Although our sample is incomplete in terms of either a fixed stellar mass or star formation rate limit, we discuss the implications that typical star-forming disk galaxies evolve to arrive on a well-defined Tully-Fisher relation within a surprisingly short period of cosmic history.</z<1.7.>